Estructuración de los procesos administrativos en los departamentos de la unidad de atención ambulatoria del IESS - Calceta. - Barros García, Ángel David (2010)
The thesis "Structure of Administrative Proceedings of the Ambulatory Care Unit IESS Calceta" was developed based on the issues presented in this institution, with regard to the lack of a mechanism that will get a document based on the structure of the administrative processes of the different areas, this document was designed as a manual of procedures and functions that allows the unit servers know exactly their roles and responsibilities, the same unit contain a description of activities to be followed in carrying out the functions of servers who working in the unit, also this basic information is been recorded and transmitted without any distorting concerning to the operation of all administrative units, as well as facilitate audit work, assessment and internal control, surveillance, awareness among employees and their managers that the job is done properly or not. This research is been structured in five chapters. The first contains the history of this research, in the second chapter contains the theoretical framework with the several bibliographies consulted for the support of research, the third chapter contains the methodological development and the techniques used, which was the historical, descriptive and field, as well as direct observation and interview who allows development and / or investigation process, the fourth chapter contains the results, the fifth chapter conclusions and recommendations and the last part contains the bibliography and appendices.